Design of Drug‐Like Protein–Protein Interaction Stabilizers Guided By Chelation‐Controlled Bioactive Conformation Stabilization. Issue 31 (11th May 2020) - Bosica, Francesco; Andrei, Sebastian A.; Neves, João Filipe; Brandt, Peter; Gunnarsson, Anders; Landrieu, Isabelle; Ottmann, Christian; O'Mahony, Gavin
Abstract: Protein–protein interactions (PPIs) of 14‐3‐3 proteins are a model system for studying PPI stabilization. The complex natural product Fusicoccin A stabilizes many 14‐3‐3 PPIs but is not amenable for use in SAR studies, motivating the search for more drug‐like chemical matter. However, drug‐like 14‐3‐3 PPI stabilizers enabling such studies have remained elusive. An X‐ray crystal structure of a PPI in complex with an extremely low potency stabilizer uncovered an unexpected non‐protein interacting, ligand‐chelated Mg 2+ leading to the discovery of metal‐ion‐dependent 14‐3‐3 PPI stabilization potency. This originates from a novel chelation‐controlled bioactive conformation stabilization effect. Metal chelation has been associated with pan‐assay interference compounds (PAINS) and frequent hitter behavior, but chelation can evidently also lead to true potency gains and find use as a medicinal chemistry strategy to guide compound optimization. To demonstrate this, we exploited the effect to design the first potent, selective, and drug‐like 14‐3‐3 PPI stabilizers. Abstract : No PAINS, no gain ! Chelation is associated with pan‐assay interference compounds (PAINS) but can also lead to true potency gains and be exploited to guide medicinal chemistry optimization. Bivalent metal ions increased the potency of a marginally active 14‐3‐3 PPI stabilizer up to 100‐fold via stabilization of the bioactive ligand conformation. Mimicry of this by intramolecular H‐bonds led to the first potent, drug‐like 14‐3‐3 PPI stabilizers (see figure).